2018
DOI: 10.1177/0004867417748750
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of risk factors for methamphetamine-associated psychosis

Abstract: The most consistent correlates of psychotic symptoms were increased frequency of methamphetamine use and dependence on methamphetamine. The findings of this review highlight the need for targeted assessment and treatment of methamphetamine use in individuals presenting with psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 51 publications
11
47
0
1
Order By: Relevance
“…Although a literature review did not find any correlation between sociodemographic characteristics and MAP,11 our study and previous studies did find that male MA users were more likely to experience MAP 27. As two diseases in the same continuum,31 the higher risk of MAP in men appears to be in line with the findings that men are more likely than women to develop schizophrenia 32…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although a literature review did not find any correlation between sociodemographic characteristics and MAP,11 our study and previous studies did find that male MA users were more likely to experience MAP 27. As two diseases in the same continuum,31 the higher risk of MAP in men appears to be in line with the findings that men are more likely than women to develop schizophrenia 32…”
Section: Discussionsupporting
confidence: 76%
“…In early Japanese studies in which most users exclusively used MA (1955–1992), the investigators found an association between frequent and long-term use of MA and MAP 10. Based on a recent review, replicated risks factors included early-age MA use, frequent and long-term use of MA, MA dependence, alcohol and other drug use, major depressive disorders and antisocial personality disorders 11. That review found no association between sociodemographic factors and MAP.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, METH can induce a chronic psychosis in those with no premorbid psychiatric risk factors ( 54 ), suggesting that METH use can induce persistent physiological changes consistent with psychosis that are independent to genetic and personality predispositions. It is recommended that readers examine many of the comprehensive review articles available for further information on the clinical profiles, correlates, and recovery of METH-induced psychosis ( 55 60 ). Overall, METH psychosis can result in a persistent psychotic syndrome that is resistant to spontaneous recovery, and in light of the high use of METH use globally, chronic METH psychosis will undoubtedly continue to be an issue for health-care professionals.…”
Section: Chronic Methamphetamine Psychosismentioning
confidence: 99%
“…Strengths of this study included the use of a diagnostic interview (SCID I/P) to exclude pre-existing psychotic disorders, strengthening the interpretation that the symptoms observed in the sample were related to methamphetamine use. This is a key difference in comparison to a substantial number of studies in this area (40). We utilized the Brief Psychiatric Rating Scale (BPRS) (18), a well validated dimensional psychotic symptom measure that has been widely used in other studies of methamphetamine-associated psychosis (19,41) and primary psychotic disorders (42).…”
Section: Discussionmentioning
confidence: 99%